2012
DOI: 10.1103/physrevc.86.024310
|View full text |Cite
|
Sign up to set email alerts
|

Three-body properties of low-lying12Be resonances

Abstract: We compute the three-body structure of the lowest resonances of 12 Be considered as two neutrons around an inert 10 Be core. This is an extension of the bound-state calculations of 12 Be into the continuum spectrum. We investigate the lowest resonances of angular momenta and parities, 0 ± , 1 − , and 2 + . Surprisingly enough, they all are naturally occurring in the three-body model. We calculate bulk structure dominated by small-distance properties as well as decays determined by the asymptotic large-distance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 50 publications
4
56
1
Order By: Relevance
“…[2,3], we considered three-body 0 ± , 1 − , and 2 + states and suggested the most natural spinparity assignments of both bound states (0 + , 2 + , 1 − , 0 + ) and the two resonances (0 + , 1 − ). In addition, we suggested another higher-lying 2 + resonance and a signal of a 0 − structure immediately above the one-neutron threshold.…”
Section: -1mentioning
confidence: 99%
See 2 more Smart Citations
“…[2,3], we considered three-body 0 ± , 1 − , and 2 + states and suggested the most natural spinparity assignments of both bound states (0 + , 2 + , 1 − , 0 + ) and the two resonances (0 + , 1 − ). In addition, we suggested another higher-lying 2 + resonance and a signal of a 0 − structure immediately above the one-neutron threshold.…”
Section: -1mentioning
confidence: 99%
“…Our suggested assignments of 0 + and 1 − are based on structure calculations in a three-body model with two neutrons and a 10 Be core [2]. This model was successfully used to describe the four known bound states [3], and it suggested that a 0 − structure should exist [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(6) and stated in Ref. [19], the computed cross sections should be obtained in close analogy to the experimental setup, where only a finite range of final relative energies is measured, usually around a resonance in the final system. This means that the integral over E has to be performed only over this precise energy range.…”
Section: Cross Section Expressionsmentioning
confidence: 99%
“…Therefore, the question arises about a possible rotational (or in general collective) character for a sequence of continuum states of considerable width. This problem was recently investigated in previous works [19][20][21]. This was done by computation of the electric quadrupole cross sections for bremsstrahlung emission after transitions between the 8 Be states, which were described as two-body systems made of two alpha particles.…”
Section: Introductionmentioning
confidence: 99%